Effect of microarc oxidation on the properties of aluminum alloy samples - Ramazanova, Zh.M.; Zamalitdinova, M.G.; Baidauletova, M.Zh.; Kovalenko, M.V. (Kompleksnoe Ispolzovanie Mineralnogo Syra = Complex use of mineral resources, 2022)
Currently, modern manufacturing industries impose special requirements on structural materials such as aluminum, titanium, and their alloys. Various methods are used to improve the physicomechanical and corrosion properties of these materials. One of the promising ways to modify the surface in order to give it multifunctional properties is the treatment of micro-arc oxidation. A distinctive feature of the process is the formation of the oxide coatings on valve metals because of exposure to micro-arc discharges. At the same time, coatings with unique properties are formed. However, the effect of the micro-arc oxidation process on the properties of the base material has been little studied. The purpose of this work is to study the effect of the micro-arc process, implemented in pulsed mode, on the properties of oxide layers, and the base material. Modification of the alloy surface was carried out in the anode mode, with small values of the duration of the anode current pulse. An alkaline electrolyte solution was used as the electrolyte. Studies of the microhardness of the oxide layer, as well as the metal layer from the interface – oxide layer /metal deep into the metal, have shown that micro-arc discharges affect not only the properties of the oxide layer but also structural changes in the thickness of the metal. It is shown that the formed oxide coating is characterized by high microhardness. The oxide coatings obtained at the duration of the anode current pulse of 100 µs – 200 µs are wear-resistant, the coatings do not collapse, and do not wear to the ground under the accepted test conditions